FEATURES OF EXPERT PSYCHOLOGICAL COUNSELING IN EDUCATIONAL INSTITUTIONS (Psychology Travelogs, 2023)
The article deals with the issue of expert psychological counseling in institutions of general secondary education and higher educational institutions. In general, the concept of expert psychological counseling is defined. It has been established that expert psychological counseling is a process of interaction between two specialists - an expert consultant, who is a specialist in a certain field, and who turns to an expert consultant for help on topical problems that have arisen in any area of the consultant's life.Four main approaches to expert counseling are presented: Adlerian, behavioral, based on the concept of mental health and the concept of organizational development. The Adlerian approach is a psychological and educational model and proceeds from the fact that individuals, groups and communities experience a lack of information. The behavioral approach also leans toward learning, focusing on learning counseling ways to use behavioral principles in working with educational applicants and on gathering empirical data to support each influence strategy. The concept of mental health builds on the broader concept of community mental health. This type of expert counseling is based on psychodynamic theory. The goal of this approach is to help teachers and other teaching staff at the school take a fresh look at themselves and their pets. The concept of organizational development draws attention to the context in which problems arise. The review of the main levels of expert consultations in educational institutions within the framework of primary prevention was carried out and the features of the positive impact on the expert consultations of psychologists in educational institutions were considered. In conclusion, it is indicated that, given the specifics of the activities of a school psychologist, it can be argued that he is an expert consultant.
Keywords: Adlerian approach; behavioral approach; expert consultation; expert consultation model; counseling psychologist